Career Shaping of Public Relations Professionals in Poland Based On the Results of Comparative Studies - Dariusz TWORZYDLO; Norbert ZYCZYNSKI; Agata OPOLSKA-BIELANSKA (Communications of International Proceedings, 2024)
This study investigates the evolving career dynamics of public relations (PR) professionals in Poland, focussing on factors that influence career satisfaction, retention and job stability. While successful PR practice relies on skilled and motivated professionals, limited research has addressed career trajectories and challenges faced by PR specialists in Poland, particularly in response to recent global labour market changes. Addressing this gap, the study analyses key determinants of job satisfaction, career commitment and turnover intentions among Polish PR professionals, providing insight into an under-researched area within the industry. Using a comparative approach, two original surveys were conducted in 2021 and 2022 with PR professionals, employing auditory surveys and computer-assisted web interview techniques to collect data on job satisfaction, likelihood of recommending a PR career, probability of choosing PR again and frequency of considering a career change. The results reveal a significant decline in job satisfaction, along with increased consideration of career changes and growing uncertainty about the long-term value of a PR career. Additionally, more than 42% of the participants entered the field by chance rather than through deliberate planning, pointing to a lack of intentional career development within the industry. These findings underscore the need for focused career development and retention strategies to strengthen the PR profession, particularly as it faces challenges related to job stability, professional identity and employee satisfaction in a rapidly changing market landscape.
Keywords: public relations; job satisfaction; PR career shaping.